Violencia puertas adentro: la mujer golpeada - Larrain Heiremans, Soledad (Colección Punta de lanza, 1994)
"One of the best studies of patterns of domestic violence in Santiago, work shows good command of the relevant literature and uses careful survey of 1,000 women of different social strata to ascertain variables most likely to put women at risk for domestic violence"--Handbook of Latin American Studies, v. 57